Konsep Pernikahan dalam Al-Quran - Syafrudin Katili (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2010)
This article describes marriage in the Koran. Marriage implies a transaction (akad) that legitimizes the relationship between a man with one woman as husband and wife. Conducting marriage in the Koran meant protecting humans from committed the wrong-doing such as adultery which considered against the nature of the human. Principally, marriage is the only legitimate way to meet the needs of the sexual instinct, the instinct of fatherhood and motherhood and other humanitarian instincts. Therefore, the Koran strictly prohibits all forms of sexual promiscuity; and facilitates freely both in the form of monogamous and polygamy marriage within reasonable reasons in terms of balance, harmony and do not mean as persecution.